Studi Inferensi Fuzzy Tsukamoto Untuk Penentuan Faktor Pembebanan Trafo PLN - Thamrin, Fanoeel; Sediyono, Eko; Suhartono, Suhartono (Universitas Diponegoro, 2012)
One of the strategic components of the power system is the transformer. Disruption of the transformer can cause the transformer to burning and the transformer performance to decrease. Therefore, in this case maintenance and detection of damage to the transformerneeds to be done regularly so that the transformer can work within the period of maximum usage. But, the problem is the substantial costs required to ask for an expert in transformer maintenance and inspection on a regular basis. Based on these issues it is necessary to develop software with capabilities equal or close to an expert diagnosis of a transformer with high accuracy and speed of maintenance ontransformers before irreparable damage. Application of expert system with fuzzy inference Tsukamoto for PT. PLN transformer maintenance is an expert system used to detect other types of disturbances in PT PLN distribution transformers so that maintenance can be performed in accordance with the type of damage or disturbance that occurred in the transformer. This application is equipped with transformer loading calculation, an imbalance of load on trafo. Input variables used in determining transformer loading and load imbalance on the current transformer is rated at each phase transformer, the voltage of each phase, power factor and the tra nsformer capacity.Keywords : Expert System, Fuzzy Tsukamoto, Transformers Maintenance